Metody diagnostyki laboratoryjnej COVID-19 - Aleksander Michalski; Agata Bielawska-Drózd; Piotr Cieślik; Przemysław Makowski; Janusz Kocik (Wiedza Medyczna, 2020)
Numerous publications pertaining identification of SARS-CoV virus appeared from 2003. A metaanalysis of the studies has shown an effectiveness of real-time reverse transcriptase polymerase chain reaction in Coronavirus genus detection. First, the authors describe the exposure risk for the medical and laboratory personnel. There are several risk points in the chain of lab activities. The way to current standard of coronavirus is shown as well as the elements of the molecular assays. Serological test are supplementary to the RT-PCR in selected clinical scenarios. The diagnostic algorithm is proposed with the use of the combination of the tests. This is for increasing the chance of detection of SARS-CoV-2 in unsymptomatic patients, as well as mild cases under surveillance, quarantine and isolation. The serological studies may be useful in epidemiological investigations and future retrospective studies on COVID-19 pandemic.